Family Empowerment with SEDAP Method (Sharing, Education and Practice) in Improving the Quality of Life in Lung Tuberculosis Patients - Lestari Lestari; Cecep Triwibowo; Ida Nurhayati; Nita Andriani Lubis (Humanistic Network for Science and Technology (HNST), 2021)
Introduction: Family empowerment might be considered asan effort to strengthen the role and knowledge of familywith TB patients. Objective: Proving the effectiveness of family empowerment with SEDAP (Sharing, Education, and Practice) method to improve the quality of life in pulmonary tuberculosis patients. Methods: Mixed methods research, qualitative research was done using FGD approach, while pre-post control group design was used for the quantitative research. Thirty-eighttrials of TB patients were divided into 2 groups: intervention group where family empowerment was introduced using the SEDAP method and control group. Qualitative data were collected using a recording device which would be transcripted, followed by keyword observation and analysis. Quantitative data were obtained using SGRQ questionnaires, both on knowledge and quality of life variables. Qualitative data were analyzed by interactive models, whereas quantitative data by independent samples t-tests and paired samples t-test. Results: Three main domains (knowledge, attitude, and behavior) were obtained from the FGD results, along with the keywords analyzed from each domain. Knowledge domain was associated with TB causes and routes of transmission, attitude was related to the negative stigma on TB patients, and lastly, behaviour was linked with patients’ forgetfulness in taking medication and the side effects occurred due to the medication. P-value